اتفاقية سايكس-بيكو، سازانوف-باليولوك 1916 بين الامس واليوم "مقارنة بين الاسباب والنتائج لهذة الاتفاقية و مستجدات خارطة الشرق الاوسط الجديد" - صابر, سروه‌ اسعد (Sulaimani Journal for Humanities, 2018)
Abstract The events of First World War imposed on Allies (Britain، France، Tsarist Russia) the need to discuss the fate of the Ottoman state properties and how to divide it between them، with taking their interest into consideration. The Ottoman Kurdistan، which had an important geopolitical role in the middle-east had been regarded as one of those Ottoman's properties، had been divided between Russian and France. When Russian draw itself from the agreement because of October revolution in 1917، Britain became interested in getting into Mosul province in Iraq. After the World War ended on the first of November 1918 and to the 1926 manifested the forms and outlines of this agreement by the developments of these events. One of the results of this development was to inflict southern Kurdistan on Iraq، the new-constructed state، and the western Kurdistan on the state of Syria، and Northern Kurdistan remained within the State of Kemalist Turkey. The reigns of these countries were characterized as centralized and nationalistic reigns. Following that the Kurdish question would be getting a notable role in the new map of the Middle East، which is the substitute of the old Sykes-Picot agreement